Síntese de 1H-isocalcogênocromenos via NA2SE a partir de derivados de eninos - Maroneze, Adriano (2020)
In the present work, we developed the synthesis of 1H-isocalcogenochromene via a nucleophilic addition of Na2Se to enynes. The reaction parameters were studied and the results indicated that the reaction of enynes (0.25 mmol) with elemental selenium (2.0 equiv) and NaBH4 (3 equiv), under 75 ◦C, using DMF and EtOH as the solvent, was the best reaction condition, providing the products in 52-81% yield. In order to demonstrate the versatility of the synthesized products, they were subjected to reactions with different boronic acids in the presence of SeO2 and against organolithium compounds.